SORPTION OF NICKEL FROM HYDROCARBON SOLUTIONS ON CLAY MINERALS - Войтко, І.І.; Манчук, Н.М.; Баглєй, Є.В.; Лащенко, К.М.; Бабанов, В.В. (Proceedings of National Aviation University (archive), 2012)
In order to develop methods of extraction from petroleum and petroleum products explored sorption of nickel from its heptan solutions on domestic deposits kaolin and bentonite. Experimentally obtained sorption isotherms. The values of sorption capacity of these minerals are equal respectively for nickel 0.35 and 0.39 mmol/g. It is concluded that after the tests on samples of oil and oil products these natural sorbents can be recommended for use in practice.